KAJIAN REKONSTRUKSI “BUDAYA SIRI” BUGIS DITINJAU DARI PENDIDIKAN ISLAM - Subri Abdullah (Al-Ishlah: Jurnal Pendidikan Islam, 2016)
This journal discusses the "Reconstruction of Siri Culture" of Bugis viewed from Islamic Education". The purpose of this paper is to know the concept of Siri 'Bugis, the relevance of Siri' Bugis culture with Islamic education, and the internalization of educational values of Islamic education into the Siri 'Bugis-Makassar culture. Siri 'Culture Bugis is a shame (psychological condition) that decomposes into human dignity that becomes the philosophy of Bugis’ life manifested in pangngadereng (adat) as well as social life, and religious. As a philosophy of life, Siri 'became the core value of Bugis culture until now and a dynamic shift of Siri'. Islamic Education with Siri culture of 'Bugis have mutually supportive relevance (symbiosis mutualism). Islamic education is the process of cultivating character of human beings who are morally, knowledgeable, creative, innovative, guiding people to the truth as the basis of life in the world and in the hereafter. While Siri Culture 'can serve as a spirit of learners in the educational process. The value of Islamic education summarized in the value of Godhead (Divinity), Humanity, and Nature has similarity to the value of Siri 'which is summed up in the elements of Siri': Pajjama, Lempu ', Getteng, and Sipakatau. Nevertheless, the value of Siri does not summarize the overall value of Islamic education. Internalization of Islamic educational values into the Siri 'Bugis culture is a necessity as a basic value in implementing the Siri culture. Internalization can be done by transformation (education value) of Islamic education, through the educational process with the support of all elements of society. Operationally, internalization must be supported by elements of education such as curriculum, learning and adequate teacher resources.